2009
DOI: 10.1007/s00701-009-0288-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic clinical and radiological parameters for immediate facial nerve function following vestibular schwannoma surgery

Abstract: Our data suggests that the analysis of the radiological and neurological patient data prior to surgery could give reliable clues regarding the immediate post-operative facial nerve function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 40 publications
2
39
2
Order By: Relevance
“…Older patients and those with larger tumors are known to have an increased risk of facial nerve injury after microsurgery. 5,9 In larger tumors extending to the facial nerve, the nerve is at greater risk during surgery and more likely to show intraoperative electrophysiological irritation which, by the treatment methods we described, would lead us to elect an STR. This explains why patients with STR had larger tumors than patients with GTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients and those with larger tumors are known to have an increased risk of facial nerve injury after microsurgery. 5,9 In larger tumors extending to the facial nerve, the nerve is at greater risk during surgery and more likely to show intraoperative electrophysiological irritation which, by the treatment methods we described, would lead us to elect an STR. This explains why patients with STR had larger tumors than patients with GTR.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with larger tumors have consistently had worse outcomes than patients with smaller tumors after both radiosurgery and microsurgery. 5,9,21 A patient's facial nerve function before surgery is an important determinant of posttreatment outcome; patients presenting with poor preoperative facial nerve status more often have deterioration of facial nerve function than patients with a better preoperative status. 9 Age may also be an important factor to consider in treating VSs-younger patients have a higher likelihood of facial nerve preservation.…”
mentioning
confidence: 99%
“…But the results of some recent studies have not supported these conclusions. 12,14,23 Thus, we hypothesized that not all cystic VSs may have worse surgical outcomes, and some undefined factors originating from cystic VSs might be responsible for these different clinical and surgical courses. Interestingly, we found a subset of cystic VSs presented with fluid-fluid levels, indicating intratumoral hemorrhage, as previously reported.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…2,12,14,23 Lunardi et al 17 believed that aspiration of the cyst content facilitated recognition and preservation of the facial nerve and removal of the solid component, thus ensuring a very good prognosis in all patients. Mehrotra et al 20 found that in cystic VS, facial nerve preservation was higher due to the faster and earlier decompression of the lesion that facilitated its earlier identification.…”
Section: 2127mentioning
confidence: 99%
“…This is the reason why functional preservation of the facial nerve is sought when managing VS with either radiosurgery or microsurgery. Several factors have been correlated with worse facial nerve function outcomes, including older patients, large tumors, and preoperative facial nerve function 2,3,4 . Although careful facial nerve dissection is pursued, anatomical preservation of the facial nerve is not synonymous of normal function 5,6,7 .…”
mentioning
confidence: 99%